2023
DOI: 10.3390/ijerph20105854
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Media Use among Children up to the Age of 10: A Systematic Literature Review

Abstract: Introduction: Digital screen media use has significantly grown in all age groups and at an increasingly young age, including toddlers, schoolers, and primary school children. Although there is evidence that excessive early childhood media exposure can lead to several negative developmental outcomes, no systematic review on Problematic Media Use (PMU) of children under 10 years old have been provided. The aim of the present systematic review was to identify (i) the main instruments used to measure children’s PM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 142 publications
0
0
0
Order By: Relevance
“…Lin et al [21] revealed a significant correlation between the duration of television viewing and the enhancement of cognitive, language, and motor abilities in infants between the ages of 15 and 35 months. Many factors were found to have significant correlations with their respective effects, including unhealthy eating habits; increased body mass index (BMI) and risk of obesity; late-onset eating disorders; language, motor skill, and cognitive development; decline in academic success; parent-child conflict; aggressive and/or antisocial behavior; mood or hyperactivity disorder; and sleep issues [1,2,8,13,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Lin et al [21] revealed a significant correlation between the duration of television viewing and the enhancement of cognitive, language, and motor abilities in infants between the ages of 15 and 35 months. Many factors were found to have significant correlations with their respective effects, including unhealthy eating habits; increased body mass index (BMI) and risk of obesity; late-onset eating disorders; language, motor skill, and cognitive development; decline in academic success; parent-child conflict; aggressive and/or antisocial behavior; mood or hyperactivity disorder; and sleep issues [1,2,8,13,[21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%